How Infant and Toddlers’ Media Use Is Related to Sleeping Habits in Everyday Life in Italy - Bellagamba, Francesca; Presaghi, Fabio; Di Marco, Martina; D’Abundo, Emilia; Blanchfield, Olivia; Barr, Rachel (Frontiers in Psychology, 2021)
Background. Heavy media use has been linked to sleep problems in children, which may also extend to the infancy period (Cheung et al., 2017). While international parent-advisory agencies, such as the American Academy of Pediatrics (2016), advise no screen time before 18 months, parents often do not follow this recommendation. Research on Italian infants’ early access to media is sparse (Balbinot et al. 2016; Mascheroni et al. 2014), and only very few studies have investigated links with sleeping habits (Chindamo et al. 2019). Method. To address this gap, we examined concurrent associations between parent-reported surveys of child technology use and sleeping patterns. The Italian version of the 60 item Comprehensive Assessment of Family Media Exposure (CAFE) Survey, developed as part of a larger international study (Barr et al., 2020), the Brief Screening Questionnaire for Infant Sleep Problems (BISQ, Sadeh, 2004) were completed online by 264 Italian parents of 8- to 36-month-olds and a subset (n = 134) completed the Parenting Stress Index (PSI, Abidin, 1995) between April 2017 and April 2018. Results. More devices located in the child’s room and the more time spent watching TV or using an iPad were associated with less hours of sleep at night. Furthermore, more time spent watching tv or using a smartphone, as well as the number of devices in the room was associated with going to sleep later at night. Instrumental media use was associated with less sleep. Conclusions: Like other countries, Italian infants have high levels of exposure to media, and differences in media patterns were associated with sleep patterns. Cultural factors influence both instrumental reasons for media use and sleep practices. Further research should explore how media use may serve to regulate emotion as a function of both contextual factors and individual differences.